Towards a cognitive model of hallucinations in the course of alcohol dependence? A source monitoring-based pilot study. Issue 13 (October 2014) - Gawęda, Ł.; Mikuła, J.; Szelenbaum, W.; Kokoszka, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Background We investigated whether source-monitoring deficits (here a discrimination between imagined and performed actions) underlie hallucinations among patients with a history of hallucinations in the course of their alcohol dependence. Method We assessed 29 patients with alcohol dependence who had no history of hallucinations during their course of alcoholism and 29 patients with a history of at least one episode of hallucinations of any modality during their course of alcohol dependency. The control group consisted of 24 healthy participants. Participants were assessed with an action memory task. Simple actions were presented to the participants verbally or non-verbally. Some actions were performed physically and others were imagined. In the recognition phase, participants were asked whether the action was presented verbally or non-verbally (action presentation type discrimination) and whether the action was performed or imagined (self-monitoring). A confidence score related to self-monitoring responses was also obtained. Results Alcoholics with a history of hallucinations misremembered imagined actions as perceived ones more frequently than patients without hallucinations, but not the reverse. Only patients with a history of hallucinations committed more errors of this type than healthy subjects. There were no group differences regarding discrimination between an action presentation type. Both clinical groups committed errors with a higher degree of confidence than healthy subjects. Conclusions Our results tentatively suggest that a specific type of source-monitoring deficit (i.e. confusing imagery with reality) may be involved in the hallucinations in patients with alcohol dependence. The findings are discussed in the light of a transdiagnostic approach to hallucinations.